Social and economic impacts of increasing early marriages during the Covid-19 pandemic: A study in Mandailing Natal and South Tapanuli districts - Lubis, Muhlisah; Jureid, Jureid; Defriza, Rita; Kholijah, Siti; Saniah, Nur (Universitas Islam Indonesia, 2024)
IntroductionSince the Covid-19 outbreak, underage marriages have become increasingly widespread with all its impact to the society. There are very limited studies on its impact from social and economic aspect, especially among Muslim society in Indonesia.ObjectivesThe purpose of this study was to analyse the social and economic impacts of increasing underage marriage during the Covid-19 pandemic. By doing so, the study also aims to provide solution to solve the impacts for the affected communities.MethodThis study uses a qualitative method with a sociological approach that focuses on experiences and socio-cultural phenomena that occur in the midst of society.ResultsThere are several social impacts that occur as a result of early marriage, conflict in the family, regret and heavy pressure, loss of opportunity to continue education, not being able to socialize, domestic violence, divorce. The economic impacts that occur due to early marriage, among others, are limited opportunities to get work opportunities, unable to bear the family's economic burden, structural poverty.ImplicationsEfforts were made to reduce the number of early marriages, among others, holding meetings several times a month, formally coordinating community leaders, village officials, and KUA, through outreach programs to Majlis Taklim, marriage advice, through marriage sermons, coordinating with sub-districts, youth activities related to early marriage.Originality/NoveltyThe findings of this study contribute to efforts to overcome social and economic problems among Muslim society impacted by the Covid-19 pandemic.